The relationship between exercise self-efficacy, intention, and structural barriers for physical activity after a cancer diagnosis - Depenbusch, Johanna; Haussmann, Alexander; Wiskemann, Joachim; Tsiouris, Angeliki; Schmidt, Laura; Sieverding, Monika; Ungar, Nadine; Steindorf, Karen (Cancers, 2022)
Previous research has shown that structural barriers negatively influence the physical activity (PA) behavior of cancer patients, but underlying mechanisms are unclear. The aim of the current study was to explore the potential mediating role of social-cognitive factors, namely PA self-efficacy and PA intention in this context. A total of 856 cancer patients completed a questionnaire on sociodemographic and medical characteristics, pre- and post-diagnosis PA, PA self-efficacy, PA intention, and PA impediment by structural barriers. A serial mediation model was used to test whether the association between structural barriers and post-diagnosis PA was mediated by PA self-efficacy and/or PA intention, in the overall sample and in subsamples defined by individuals’ pre-diagnosis PA. The results confirmed that structural barriers were not directly (95%CI [−0.45; 0.10]) but indirectly associated with post-diagnosis PA. Higher impediment by structural barriers decreased the likelihood of sufficient post-diagnosis PA via lower PA self-efficacy (95%CI [−0.25; −0.06]) and via the serial pathway of lower PA self-efficacy and lower PA intention (95%CI [−0.19; −0.05]). Investigating differences in these mediations by pre-diagnosis PA yielded significance only among previously active cancer patients. Both structural barriers and PA self-efficacy might hence be relevant target points for interventions aiming to improve PA behavior, especially among pre-diagnosis active cancer patients.
Gesehen am 14.07.2022
This article belongs to the special issue "Physical activity and cancer care"